Global Administrative Governance: Liberalization of Government Procurement in Third World Countries - Suherman, Ade Maman (Indonesian Journal of International Law, 2021)
Globalization and the rise of global governance are transforming the structure of International law. From the perspective of the classical, interstate consent-based international law, global governance may still appear merely as a quantitative increase in international legal instruments. On the other hand, some requirement for adoption international law is needed, particularly through a classic scheme for binding force of international law into national legal system. Classic method means that such agreement which is concluded by states. One of the interstate consent based international law is Government Procurement Agreement (GPA) which legally binding agreement in the WTO focusing on the subject of government procurement. Since GPA is a multilateral treaty administered by a Committee on Government Procurement, which includes the WTO Members that are parties to the GPA, and thus have rights and obligations under the Agreement. In fact, the majority of member state, particularly most developing countries are not party the GPA, so there is no legal obligation to observe all the provision of GPA. It seems to be a great obstacle for developing countries to adopt the GPA provisions by several reasons In sum, global administrative governance takes some roles to reform some legal frame works in developing countries. A great contribution produced some positive legal reforms in term of the achievement of competitive and transparent government procurement.